Umbilical Cord Mesenchymal Stem Cells Promoting Spinal Cord Injury Repair Visually Monitored by AIE‐Tat Nanoparticles (Adv. Therap. 12/2022). Issue 12 (14th December 2022) - Xie, Peigen; Ling, Haiqian; Pang, Mao; He, Lei; Zhuang, Zeyan; Zhang, Guiling; Chen, Zihao; Weng, Chuanggui; Cheng, Sijin; Jiao, Ju
Abstract : In article number 2200076, Ju Jiao, Zujin Zhao, Ben Zhong Tang, Limin Rong, and co‐workers report that ultrabright red nanoparticles based on aggregation‐induced emission luminogens, taking advantage of high resistance to photobleaching and excellent biocompatibility, can provide crucial information on the viability, distribution, migration, and proliferation of transplanted human umbilical cord mesenchymal stem cells in spinal cord injury models, which will inspire the development of stem cell‐targeting reagents for in vivo applications.